A unified personal protective equipment ensemble for clinical response to possible high consequence infectious diseases: A consensus document on behalf of the HCID programme. Issue 6 (December 2018) - Poller, Bozena; Tunbridge, Anne; Hall, Samantha; Beadsworth, Mike; Jacobs, Mike; Peters, Erica; Schmid, Matthias L; Sykes, Allison; Poran, Vin; Gent, Nick; Evans, Cariad; Crook, Brian; et al.
Highlights: Potential safety issues have been identified with current PPE ensembles for HCID. Our novel simulation model tests PPE for both bodily fluid and airborne pathogens. A new consensus model of PPE for HCID is proposed, with supporting safety data. The model is explained, together with protocols for donning and doffing PPE safely. It has been agreed by a working group of expert stakeholders from around the UK. Summary: The importance of appropriate personal protective equipment (PPE) as a component of healthcare worker (HCW) protection was highlighted during the Ebola virus disease (EVD) outbreak in West Africa. The large number of HCW deaths in Africa was in part due to lack of resources or prior training in PPE usage. As part of the Ebola legacy, the High Consequence Infectious Disease (HCID) programme was initiated by NHS England and Public Health England (PHE) to improve preparedness for Ebola and other infections that not only endanger the life of the patient, but also pose particular dangers to HCWs. A systematic review identified national standardisation of PPE protocols as a priority, but recognised that a lack of safety data limited the ability to mandate any one protocol. A simulation-based exercise was developed to assess the safety of PPE ensembles in use in the UK during first assessment of a patient with a possible HCID. A mannequin was adapted to expose volunteer HCWs to synthetic bodily fluids (vomit, sweat, diarrhoea and cough), each with a different coloured fluorescent tracer, invisible other than under ultraviolet (UV) light. After exposure, HCWs were examined under UV lights to locate fluorescent contamination, and were screened again after removing PPE (doffing) to detect any personal contamination. The exercise was videoed, allowing retrospective analysis of contamination events and user errors. The simulation testing identified significant HCW contamination events after doffing, related to protocol failure or complications in PPE doffing, providing conclusive evidence that improvements could be made. At a workshop with an expert stakeholder group, the data were examined and a unified PPE ensemble agreed. This ensemble was then tested in the same simulation exercise and no evidence of any HCW contamination was seen after doffing. Following further review by the working group, a consensus agreement has been reached and a unified 'HCID assessment PPE' ensemble, with accompanying donning and doffing protocols, is presented here.